Upaya Pengembangan Potensi Wisata Alam di Desa Wonomerto Sebagai Daya Tarik Wisata Desa - Adhelia Salwa; Kusuma Wardhani Mas'udah; Hasri Maghfirotin Nisa; Anggi Dian Lestari; Sindi Astutik; Imron; Raden Mas Anugrah Eko Rahmanto (CV. Multi Kreasi Media, 2022)
Wonomerto Village, Wonosalam District, Jombang Regency has very interesting natural tourism potential. Various natural attractions such as mountains, rivers, plantations, forests, and cultural heritage sites that are no less charming. However, this tourist attraction is still not optimal in terms of several aspects. This study aims to determine the efforts to develop natural tourism potential in Wonomerto Village and what factors influence the efforts to develop tourism objects. The theory used is Kuswan's theory regarding the strategic aspects of developing natural tourism objects which include Development Planning Aspects, Institutional Aspects, Facilities and Infrastructure Aspects, Management Aspects, and Marketing Aspects. The author uses a qualitative descriptive research method with the informants are tourism managers in Wonomerto Village, data collection techniques are carried out by interviews, observation, and documentation. The results of research efforts to develop Wonomerto Village into one of the natural tourist attractions in Jombang Regency can be concluded that it is not optimal because the development planning targets are not yet optimal, many institutional structures have not been formed, facilities and infrastructure that need maintenance and repair, management is not optimal, lack of digital branding or promotion and lack of collaboration with external parties.